Modeling optimal long-term investment strategies of hybrid wind-thermal companies in restructured power market - Askari M.T.; Kadir M.Z.A.A.; Tahmasebi M.; Bolandifar E. (Springer Heidelberg, 2023)
Commerce; Data mining; Dynamic programming; Game theory; Markov processes; Monte Carlo methods; Power markets; Stochastic systems; Strategic planning; Wind power; Cournot game theory; Generation expansion planning; Stochastic dynamic programming; Uncertainties; Wind resources; Investments